Identification of the transporter responsible for sucrose accumulation in sugar beet taproots. - Jung, Benjamin; Ludewig, Frank; Schulz, Alexander; Meißner, Garvin; Wöstefeld, Nicole; Flügge, Ulf-Ingo; Pommerrenig, Benjamin; Wirsching, Petra; Sauer, Norbert; Koch, Wolfgang; Sommer, Frederik; Mühlhaus, Timo; et al. (Nature Plants, 2015)
Sugar beet provides around one third of the sugar consumed worldwide and serves as a significant source of bioenergy in the form of ethanol. Sucrose accounts for up to 18% of plant fresh weight in sugar beet. Most of the sucrose is concentrated in the taproot, where it accumulates in the vacuoles. Despite 30 years of intensive research, the transporter that facilitates taproot sucrose accumulation has escaped identification. Here, we combine proteomic analyses of the taproot vacuolar membrane, the tonoplast, with electrophysiological analyses to show that the transporter BvTST2.1 is responsible for vacuolar sucrose uptake in sugar beet taproots. We show that BvTST2.1 is a sucrose-specific transporter, and present evidence to suggest that it operates as a proton antiporter, coupling the import of sucrose into the vacuole to the export of protons. BvTST2.1 exhibits a high amino acid sequence similarity to members of the tonoplast monosaccharide transporter family in Arabidopsis, prompting us to rename this group of proteins 'tonoplast sugar transporters'. The identification of BvTST2.1 could help to increase sugar yields from sugar beet and other sugar-storing plants in future breeding programs.

Routes to the tonoplast: the sorting of tonoplast transporters in Arabidopsis mesophyll protoplasts. - Wolfenstetter, Susanne; Wirsching, Petra; Dotzauer, Dorina; Schneider, Sabine; Sauer, Norbert (The Plant Cell, 2012)
Vacuoles perform a multitude of functions in plant cells, including the storage of amino acids and sugars. Tonoplast-localized transporters catalyze the import and release of these molecules. The mechanisms determining the targeting of these transporters to the tonoplast are largely unknown. Using the paralogous Arabidopsis thaliana inositol transporters INT1 (tonoplast) and INT4 (plasma membrane), we performed domain swapping and mutational analyses and identified a C-terminal di-leucine motif responsible for the sorting of higher plant INT1-type transporters to the tonoplast in Arabidopsis mesophyll protoplasts. We demonstrate that this motif can reroute other proteins, such as INT4, SUCROSE TRANSPORTER2 (SUC2), or SWEET1, to the tonoplast and that the position of the motif relative to the transmembrane helix is critical. Rerouted INT4 is functionally active in the tonoplast and complements the growth phenotype of an int1 mutant. In Arabidopsis plants defective in the β-subunit of the AP-3 adaptor complex, INT1 is correctly localized to the tonoplast, while sorting of the vacuolar sucrose transporter SUC4 is blocked in cis-Golgi stacks. Moreover, we demonstrate that both INT1 and SUC4 trafficking to the tonoplast is sensitive to brefeldin A. Our data show that plants possess at least two different Golgi-dependent targeting mechanisms for newly synthesized transporters to the tonoplast.